(3JGQjN GdESdGe hWHbGJ GdeTGgjQ hGdCYdGes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3GdWHbI GdSGHYI hGdYTQhf SfI EMOi hSJjf heGFJjf Jhai ajgG CMeO Hf SdjeGf GdQgGhi s
(3BNQgG (B:s
(3BNQ GdehLhO efg (B: (3jYbhH Hf CMeO Hf CSO GdSGeGfi GdCejQ eJhdi Sei JfOeGJ s
(3HgG fXGe GdJYbjHIs
(3Ydjg JedcGJ CbOGegG (B1271 (3SfIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs